Thermal Inactivation of Enteric Viruses and Bioaccumulation of Enteric Foodborne Viruses in Live Oysters (Crassostrea virginica) - Araud, Elbashir (Appl Environ Microbiol, 2016)
Human enteric viruses are among the main causative agents of shellfish-associated outbreaks. In this study, the kinetics of viral bioaccumulation in live oysters and the heat stabilities of the predominant enteric viruses were determined both in tissue culture and in oyster tissues. A human norovirus (HuNoV) GII.4 strain, HuNoV surrogates (murine norovirus [MNV-1], Tulane virus [TV]), hepatitis A virus (HAV), and human rotavirus (RV) bioaccumulated to high titers within oyster tissues, with different patterns of bioaccumulation for the different viruses. We tested the thermal stability of each virus at 62, 72, and 80°C in culture medium. The viruses can be ranked from the most heat resistant to the least stable as follows: HAV, RV, TV, MNV-1. In addition, we found that oyster tissues provided protection to the viruses during heat treatment. To decipher the mechanism underlying viral inactivation by heat, purified TV was treated at 80°C for increasing time intervals. It was found that the integrity of the viral capsid was disrupted, whereas viral genomic RNA remained intact. Interestingly, heat treatment leading to complete loss of TV infectivity was not sufficient to completely disrupt the receptor binding activity of TV, as determined by the porcine gastric mucin–magnetic bead binding assay. Similarly, HuNoV virus-like particles (VLPs) and a HuNoV GII.4 strain retained some receptor binding ability following heat treatment. Although foodborne viruses have variable heat stability, 80°C for >6 min was sufficient to completely inactivate enteric viruses in oysters, with the exception of HAV.